Polycystic ovary syndrome is associated with severe platelet and endothelial dysfunction in both obese and lean subjects - Rajendran, Sharmalar; Willoughby, Scott R.; Chan, Wai Ping A.; Liberts, Elizabeth A.; Heresztyn, Tamila; Saha, Mrinal; Marber, Michael S.; Norman, Robert J.; Horowitz, John D. (Atherosclerosis, 2009)
Platelet hyporesponsiveness to the anti-aggregatory effects of nitric oxide (NO) occurs commonly in association with myocardial ischemia and coronary risk factors, often co-exists with endothelial dysfunction and represents an independent marker of long-term cardiovascular risk. We sought to determine whether polycystic ovary syndrome (PCOS), which has been postulated as a cardiovascular risk factor in women, is independently associated with this phenomenon. Twenty-four young women with PCOS (mean age 32.1 ± 1.3) were evaluated in lean ( n = 12) and obese ( n = 12) subgroups, and compared with age-matched lean normals ( n = 12). Platelet aggregation and its inhibition by the nitric oxide donor sodium nitroprusside (SNP) were assessed and compared with vascular endothelial function. Plasma concentrations of malondialdehyde (MDA), N G , N G -dimethyl- l-arginine (ADMA) and hs-CRP were measured as markers of oxidative stress, endothelial dysfunction and inflammation, respectively. Circulating endothelial progenitor cell (EPC) counts were also documented. In both PCOS subgroups, which demonstrated hyperaggregability to ADP, responses to SNP inhibition of aggregation (the principal end-point of the study) were significantly impaired ( P < 0.01 for both), as were their endothelium-dependent vascular responses to salbutamol ( P < 0.05 for both). However, vasomotor responses to nitroglycerin and circulating EPC counts did not vary between groups. PCOS subjects also had significantly elevated ADMA, MDA and hs-CRP levels relative to normals (all P < 0.05). Impairment of SNP response remained unaltered after mean 30 ± 2.4 months follow-up in PCOS subjects. We conclude that in PCOS subjects, independent of obesity and associated insulin resistance, profound and reproducible impairment of platelet responsiveness to NO is an additional component of cardiovascular homeostatic disturbance.